2022
DOI: 10.1111/acel.13584
|View full text |Cite
|
Sign up to set email alerts
|

Acidic nanoparticles protect against α‐synuclein‐induced neurodegeneration through the restoration of lysosomal function

Abstract: Parkinson's disease (PD) is an age-related neurodegenerative disorder characterized by the loss of dopaminergic neurons in the substantia nigra, associated with the accumulation of misfolded α-synuclein and lysosomal impairment, two events deemed interconnected. Protein aggregation is linked to defects in degradation systems such as the autophagy-lysosomal pathway, while lysosomal dysfunction is partly related to compromised acidification. We have recently proven that acidic nanoparticles (aNPs) can re-acidify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 61 publications
0
31
0
Order By: Relevance
“… 20 , 46 Additionally, nanoparticles can also act as bioactive nanomedicines to clear abnormally aggregated proteins by modulating the autophagy-lysosomal pathway (ALP) and the ubiquitin proteasome system (UPS) pathways. 47 , 48 …”
Section: Nanotherapeutic Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“… 20 , 46 Additionally, nanoparticles can also act as bioactive nanomedicines to clear abnormally aggregated proteins by modulating the autophagy-lysosomal pathway (ALP) and the ubiquitin proteasome system (UPS) pathways. 47 , 48 …”
Section: Nanotherapeutic Strategiesmentioning
confidence: 99%
“…20,46 Additionally, nanoparticles can also act as bioactive nanomedicines to clear abnormally aggregated proteins by modulating the autophagy-lysosomal pathway (ALP) and the ubiquitin proteasome system (UPS) pathways. 47,48 In addition, nanomaterials can also be used for imaging/contrast/tracing in neurodegenerative disease treatment. Nanomaterials including rare-earth fluorescent materials, metal nanoclusters as well as quantum dots (QDs) can be exploited as fluorescent agents for bioimaging.…”
Section: Nanotherapeutic Strategiesmentioning
confidence: 99%
“…In LB-injected mice, we noticed that lysosomal function is impaired by the mislocalization of these organelles within the cell. When the lysosomes are functional, they are predominantly located around the nucleus, and their increased distance to the nucleus demonstrates their inactivity [39][40][41]. Our study showed that when LB mice were treated with ClQ, the number of lysosomes located close to the nucleus was increased compared to untreated LB-injected mice.…”
Section: Discussionmentioning
confidence: 56%
“…Figure 3B). Second, we examined whether a change in cellular localization of lysosomes could be observed, as an index of the lysosomal function [39]. Functional lysosomes are preferentially located in the perinuclear region, whereas dysfunctional lysosomes are further from the nucleus [40,41].…”
Section: Resultsmentioning
confidence: 99%
“…4 Thus, therapeutic approaches targeting lysosomes to favor an impaired pH decrease have been proven to be a promising strategy in animal models. 5,6 Nevertheless, there was a lack of systems to achieve lysosomal acidification in therapeutics. Some acid-based molecules have shown interesting properties; in particular, poly(DL-lactide-co-glycolide) (PLGA) has been described as an efficient acidifying active ingredient 7 that releases two monomers: lactic acid and glycolic acid.…”
Section: ■ Introductionmentioning
confidence: 99%